Supporting Career Progression Through Academic Mentorship (STREAM) : Final Report of the Project Developing and Implementing a Leadership Capacity Building Program for Teaching and Learning in Nursing. - Halcomb, Elizabeth; Andrew, Sharon; Peters, Kath; Salamonson, Yenna; Daly, John; Jackson, Debra; Gray, Joanne (Office for Learning and Teaching, 2014)
An acute shortage of nurse academics is leading to a rise in the number of new academics entering nursing faculties to service the growing student enrolments. Currently, despite the recognition of leadership capacity building as a priority for the nursing profession, there are limited leadership development opportunities for new nurse academics. This is the final report from a project that described an innovative model of leadership capacity development targeted at early career nurse academics (ECNAs). The model comprised of an ongoing mentoring program, four face-to-face workshops, two online modules and peer networking. Data collection included online surveys, semi-structured interviews and project evaluation data. The project findings demonstrated that orientation and capacity building programs could do more to facilitate transition into academia and building of leadership capacity. Nurse academics face a number of challenges that are likely unique to practice disciplines. Participants were not only new to the academic workplace but were also trying to balance competing demands of personal commitments and doctoral education. Participation in this leadership program was highly valued by most participants. In particular, participants valued the time, space and support to focus on their professional development. However to facilitate participation, professional development programs need to be clearly integrated into the academic workload and performance planning processes.